Perception about substance abuse among the medical students in Visakhapatnam, India: a qualitative research - Santosh, Pissey Saikiran; Arvind, Nivetha; Bhimarasetty, Devi Madhavi; Sivapriya, Jalakam Venkata (International Journal Of Community Medicine And Public Health, 2023)
Background: Substance abuse is an emerging disorder of global concern. In India about 14.6% of the population (between 10 and 75 year of age) uses alcohol. Also, 28.6 percent (266.8 million) of adults in India, aged 15 and above currently use tobacco in some form. Youth period is an important transition period where students may begin to consume alcohol, tobacco, and other substances. Methods: A Qualitative approach using systematic methods i.e., Free listing & Pile sorting, Conducted among third professional year students in a Medical College of North coast Andhra Pradesh. Analysed by Cultural domain analysis using Visual Anthropac Pile sort version1.0.1.36 based on salience scores. Results: A total of 13 medical students were included. Among them 9 (69%) were females and 4(31%) were males. Stress was found to be the major cause for substance abuse with salience score of 0.418, followed by peer pressure (0.402). The solutions for among them parental guidance is the best solution for substance abuse with highest salience score of 0.412, followed by awareness about consequences (0.409). Conclusions: Our study reveals that it is necessary to bring positive behavioural changes through adoption of comprehensive interventions, counselling methods and health education in medical universities.